Modernisasi Lembaga Pendidikan Pesantren Yayasan Al-Wustho Pabuaran Subang - Hermawan, Iwan; Suhartini, Andewi; Ahmad, Nurwadjah (Universitas Islam Negeri Raden Intan Lampung, 2020)
The modernization of Islamic boarding schools is one of the attitudes and solutions for Islamic boarding schools to continue to exist in meeting the needs of education in Indonesia. The Al-Wustho Foundation, from its inception, has combined formal school and non-formal Islamic boarding schools, as well as informal and family guidance models. By implementing collective management, the Al-Wushto foundation has gained the trust of the surrounding community and even people outside the district by entrusting their children to get general and religious education to become human beings who are beneficial to religion, the state, and the nation. The purpose of this research is to reveal the modernization of the boarding school education institution of the Al-Wustho Pabuaran Subang foundation in terms of transformative leadership styles, collective management, and a combination of formal and formal curricula so that it becomes an accredited institution. With the case study method and descriptive qualitative approach, the author tries to reveal all activities at the Al-Wustho foundation through observation, interviews, and data tracing so that something unique and different from all its weaknesses and strengths is found from the typology of Islamic boarding schools in general. Keywords: Modernization, Islamic Education, Islamic Boarding Schools, Foundations